The Reactions of Muskoxen to Snowmobile Harassment - McLaren, Margaret A.; Green, Jeffrey E. (ARCTIC, 1985)
Twenty-one harassment trials on 14 muskox herds were conducted in April and May 1982 on eastern Melville Island, N.W.T. Each trial consisted of a slow approach directly toward the herd on a snowmobile. The snowmobile, returned along its approach path as soon as 50% of the herd was alerted. Distance at which the first animal reacted (IRD) averaged 345.0 m(range 162-650 m) and the distance from the herd at closest approach (CAD) averaged 267.2 m(range 87-645 m). IRD was positively correlated with wind speed. No correlation between CAD and any of the measured variables was found. Maximum reaction level of the herd was positively correlated with herd size (rs = 0.488, P<0.05). No significant differences in IRD or CAD were found between or among classes of discrete variables such as topography and wind direction, but sample sizes were small. Adult female muskoxen reacted first more frequently than expected (P<0.02). Two herds were approached repeatedly (one six times and one three times) to assess habituation. Results were inconclusive. IRD for the herd that was approached three times decreased progressively. IRD for a herd approached six times was variable but shortest on the sixth approach and the reaction level of the herd also was low on the sixth approach.Key words: muskoxen, harassment, snowmobile, Melville Island, N.W.T. Mots clés: boeuf musqué, harcèlement, motoneige, île Melville, T.N.-O.